Trend Toward Individualization of the Endocrine and Exocrine Portions of the Giant Anteater Pancreas (Myrmecophaga Tridactyla, Xenarthra) - Iglesias, Luciana Pedrosa; Favaron, Phelipe Oliveira; Borghesi, Jessica; Oliveira Carreira, Ana Claudia; Miglino, Maria Angelica; Ferraz de Melo, Alan Perez [UNESP] (Wiley-Blackwell, 2017)
Considering the physiological importance of the pancreas as an endocrine and exocrine organ, this study described the characteristics of the gross and microscopic morphology of this organ using 16 Myrmecophaga tridactyla individuals. The pancreas was located in the left antimere of the body, was pale in colour and exhibited an elongated shape with a central body and lobulated surface. It was positioned in the abdomen, following the curvatura ventriculi major of the stomach, and was attached to the initial portion of the duodenum. The corpus pancreatis was elongated and showed a caudal curvature of 45 degrees. The pancreas exhibited a facies dorsalis (related to the spleen and stomach) and a facies ventralis (related to the renal capsule and intestine). Macroscopically, a craniodorsal, medial, and caudoventral regions were identified, in addition to the left lobe. Structurally, the organ exhibited two distinct parts: the first had exocrine characteristics, consisting of acini and ducts; the second, which was the endocrine portion, consisted of the pancreatic islets, which were located in the medial, caudoventral and left lobe regions. Ultrastructural analysis identified secretory vesicles containing zymogen granules, mitochondria, Golgi apparatus and rough endoplasmic reticulum in pancreatic centroacinar cells. Morphological data on the anatomy of members of the Xenarthra have revealed important peculiarities of several organs and systems, adding great biological value to the representatives of this group. In addition, these studies significantly contribute not only to knowledge of the biology, taxonomy and, consequently, preservation of these animals but also to the discovery of new experimental models. (C) 2016 Wiley Periodicals, Inc.
Keywords: endocrine organs; pancreatic acini; pancreatic islets; Xenarthra